1998ネン 3ガツ 25ニチ ナンキョク プレート ナイ ノ キョダイ ジシン - 東野, 陽子; トウノ, ヨウコ; 神沼, 克伊; カミヌマ, カツタダ; Tono, Yoko; Kaminuma, Katsutada (1998)
P(論文) 1998年3月25日03時12分(UT)頃, 南極プレート内の62.876°S, 149.712°Eで, M_s8.0の巨大地震が発生した。昭和基地(SYO : 69°00′S, 39°35′E)からの問い合わせに対し, フランスのDumont d'Urville基地(DRV : 66°40′S, 140°01′E)では全員が揺れを感じ, 落下物もあったと言うから日本の気象庁震度階でIII～IVに相当する。昭和基地では4時間にわたり連続して地震動が記録された。DRVの震央距離は670kmであるから, 日本の関東地震(1923年, M=7.9)を岡山付近で感じたことになり, 有感半径が700kmの関東地震と同じ規模かそれ以上の大きな地震だったことが分かる。この地震は南極プレート内で起こった初めてのM8クラスの地震であり, 南極大陸での初めての有感地震であった。 A great earthquake occurred in the Antarctic Plate at 03h 12m 24.7s (UT) on 25 March 1998. The location and magnitude of the earthquake determined by United States Geological Survey are as follows : 62.876°S, 149.712°E, 10km depth m_b 6.8,M_s 8.0. In response to a request for earthquake information from Syowa Station (69°00′S, 39°35′E) to Dumont d'Urville Station of France (66°40′S, 140°01′E), the station leader reported that all wintering members in the station felt a quake and something on the shelf in the building fell down. The intensity at the station was estimated to be III∿IV by the intensity scale of Japanese Meteorological Agency. This earthquake is the first great earthquake of magnitude 8 recorded in the Antarctic Plate since IGY of 1957 and the first earthquake felt in Antarctica except for volcanic earthquakes. departmental bulletin paper